Dose-dependent bioavailability and CYP3A inhibition contribute to non-linear pharmacokinetics of voriconazole - Hohmann, Nicolas; Kocheise, Franziska; Carls, Alexandra; Burhenne, Jürgen; Weiß, Johanna; Haefeli, Walter E.; Mikus, Gerd (Clinical pharmacokinetics, 2016)
Voriconazole is both a substrate and a potent inhibitor of cytochrome P450 (CYP) 3A. It has a high bioavailability and non-linear pharmacokinetics. We investigated the pharmacokinetics and metabolism of 50 mg and 400 mg doses of intravenous and oral voriconazole in 14 healthy volunteers. Concurrently, we determined systemic and presystemic CYP3A activity with microdosed midazolam. Bioavailability of voriconazole 50 mg was 39 % compared with 86 % of the 400 mg dose. Voriconazole area under the concentration-time curve extrapolated to infinity (AUC∞) was 416 and 16,700 h·ng/mL for the 50 and 400 mg oral doses, respectively, and 1110 and 19,760 h·ng/mL for the 50 and 400 mg intravenous doses, respectively. Midazolam metabolism was dose-dependently inhibited by voriconazole. Dose-dependent autoinhibition of CYP3A-dependent first-pass metabolism and systemic metabolism is a possible explanation for the dose-dependent bioavailability and elimination of voriconazole, either as additional mechanism to, or instead of, saturation of presystemic metabolism. Higher bioavailability and non-linear pharmacokinetics are expected to be a common property of drugs that are substrates and inhibitors of CYP3A, e.g. clarithromycin.
Gesehen am 05.01.2017